A Model for Predicting Cation Selectivity and Permeability in AMPA and NMDA Receptors Based on Receptor Subunit Composition - Kumar, Sampath; Kumar, Sanjay S. (Frontiers in Synaptic Neuroscience, 2021)
Glutamatergic AMPA (α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid) and NMDA (N-methyl-D-aspartate) receptors are implicated in diverse functions ranging from synaptic plasticity to cell death. They are heterotetrameric proteins whose subunits are derived from multiple distinct gene families. The subunit composition of these receptors determines their permeability to monovalent and/or divalent cations, but it is not entirely clear how this selectivity arises in native and recombinantly-expressed receptor populations. By analyzing the sequence of amino acids lining the selectivity filters within the pore forming membrane helices (M2) of these subunits and by correlating subunit stoichiometry of these receptors with their ability to permeate Na+ and/or Ca2+, we propose here a mathematical model for predicting cation selectivity and permeability in these receptors. The model proposed is based on principles of charge attractivity and charge neutralization within the pore forming region of these receptors; it accurately predicts and reconciles experimental data across various platforms including Ca2+ permeability of GluA2-lacking AMPARs and ion selectivity within GluN3-containing di- and tri-heteromeric NMDARs. Additionally, the model provides insights into biophysical mechanisms regulating cation selectivity and permeability of these receptors and the role of various subunits in these processes.